Strengthening and Empowering Smart Parenting in Communities to Realize Gender Sensitivity and Equity in Families - Daulay, Harmona; Sukarja, Detania (Universitas Sumatera Utara, 2025)
In order to support the SDGs program which is also relevant to Presidential Instruction No. 9 of 2000 concerning Gender Mainstreaming (PUG), various efforts are needed by the government together with the community to practice social habitus to uphold gender equality and justice. Parents (Parenting) provide affection, protection, socialization and so on. This parenting role provides an overview of parents ideally carrying out parenting roles with knowledge of educating children, social insight, PUG insight and gender equality as well as legal insight. Moving from this condition, the community service team sees the importance of strengthening and empowering the parenting community to be given insight and knowledge of gender sensitivity and various laws and regulations related to the role of parents and children's rights in the family. This is assumed to be an effort to take preventive action against events and legal consequences so that they can be prevented as early as possible. Partnering with Ranggi Literacy House which carries out various parenting strengthening in communities that are marginalized communities. the implementation of community service is carried out by providing insight into gender sensitivity, socialization and gender justice education sociologically in the practice of habitus and combining this legal insight where this is a basic right for children to receive legal protection.